Isolation and Identification of Marine Bacteria in Raja Ampat Islands West Papua Producing Antibacterial Against Salmonella typhi and Staphylococcus aureus - Mahdiyah, Dede; Dharmawan, Muhammad Rifqi; Noval, Noval (Borneo Journal of Pharmacy, 2024)
Indonesia's vast archipelago harbors a wealth of natural resources, including marine bacteria with potential antibacterial properties. Given the increasing prevalence of antibiotic resistance, particularly against Salmonella typhi and Staphylococcus aureus, there is a pressing need to explore alternative antimicrobial agents. This study aimed to isolate and characterize marine bacteria with antibacterial activity and evaluate their efficacy against S. typhi and S. aureus. Isolation of marine bacteria was conducted using the spread plate method. Antibacterial activity screening of the secondary metabolites was performed using the well diffusion method. Minimum inhibitory concentration (MIC) was determined using the dilution method, while minimum bactericidal concentration (MBC) was determined using the spread plate method. Seven bacterial isolates were obtained, all identified as Gram-negative bacilli. The secondary metabolites of these marine bacteria demonstrated antibacterial activity against both S. typhi and S. aureus, with inhibition zones of 8.50 mm and 8.46 mm, respectively. The MIC for both bacteria was determined to be 1500 μg/mL. Statistical analysis revealed a significant difference in antibacterial activity between the isolates (Kruskal-Wallis Test, p-value = 0.007) and between S. typhi and S. aureus (Mann-Whitney Test, p-value = 0.025). While the secondary metabolites exhibited antibacterial activity against both bacteria, they did not demonstrate bactericidal activity as measured by the MBC test.